Altered Blood Levels of Vitamin D, Cathelicidin and Parathyroid Hormone in Patients with Sepsis—a Pilot Study. Issue 1 (January 2017) - Greulich, T.; Regner, W.; Branscheidt, M.; Herr, C.; Koczulla, A. R.; Vogelmeier, C. F.; Bals, R.
It has been recognised that vitamin D (VitD) has a potential role in the regulation of inflammation and protection from infection. In a prospective clinical observational pilot study, we investigated the serum levels of 25-hydroxyvitamin-D3 (25(OH D3), 1, 25-hydroxyvitamin-D3 (1, 25(OH)2D3), parathyroid hormone (PTH), and cathelicidin in intensive care unit (ICU) patients with or without systemic inflammatory response syndrome (SIRS). We included 32 patients with SIRS (septic patients), 16 ICU patients without SIRS, and 16 healthy controls. To substantiate the findings of the clinical study, we stimulated monocyte-derived macrophages with microbial patterns and analysed the impact of VitD on release of cytokines and antimicrobial activity. We found that patients with or without SIRS had relatively low levels of 25(OH)D3 and 1, 25(OH)2D3. Patients with sepsis had significantly lower levels of 25(OH)D3 as compared to ICU control patients and healthy controls (10.53 ± 11.3 μg/l versus 16.46 ± 12.58 μg/l versus 24.04 ± 12.07 μg/l); the same was true for 1, 25(OH)2D3. Serum levels of PTH and cathelicidin were significantly increased in sepsis patients, as compared to the other groups. In vitro, VitD significantly decreased the release of pro-inflammatory cytokines from macrophages and increased the antimicrobial activity of the cells. We concluded that patients with sepsis have significantly lower VitD levels. In vitro, VitD modulates inflammation and increases the antibacterial activity of innate immune cells. These findings suggest that VitD insufficiency is mechanistically related to increased susceptibility to SIRS and sepsis.